2005
DOI: 10.1158/0008-5472.can-05-0591
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Latent Membrane Protein 1 (CAO) Up-regulates VEGF and TGFα Concomitant with Hyperlasia, with Subsequent Up-regulation of p16 and MMP9

Abstract: EBV latent membrane protein 1 (LMP1) is an oncoprotein frequently expressed in nasopharyngeal carcinoma. We have generated transgenic mice expressing the nasopharyngeal carcinoma-derived CAO strain of LMP1 and LMP1 of the B95-8 strain, using the viral ED-L2 promoter for epithelial expression. LMP1(CAO) and LMP1(B95-8) induce transforming growth factor alpha expression and epidermal hyperplasia. However, levels of total epidermal growth factor receptor (EGFR) decline with the appearance of phosphorylated EGFR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 48 publications
1
61
1
Order By: Relevance
“…Of particular interest was that many fell into the categories of inflammatory and wound-response genes (Table 1, Figs 3 and 6). Increased expression of many of these classes has been reported in hyperproliferative and inflamed epidermis and is consistent with previous observations demonstrating that LMP1 induces hyperproliferative lesions in transgenic murine epidermis (Stevenson et al, 2005;Wilson et al, 1990). The induction of several of these genes (IL6, IL8, VEGF, CXCL1, 2, 3, CSF2, CCL5, CCL20, BIRC3, TNFAIP3, NFKBIA and IER3) ( Table 1, Fig.…”
Section: Differentially Expressed Genessupporting
confidence: 91%
“…Of particular interest was that many fell into the categories of inflammatory and wound-response genes (Table 1, Figs 3 and 6). Increased expression of many of these classes has been reported in hyperproliferative and inflamed epidermis and is consistent with previous observations demonstrating that LMP1 induces hyperproliferative lesions in transgenic murine epidermis (Stevenson et al, 2005;Wilson et al, 1990). The induction of several of these genes (IL6, IL8, VEGF, CXCL1, 2, 3, CSF2, CCL5, CCL20, BIRC3, TNFAIP3, NFKBIA and IER3) ( Table 1, Fig.…”
Section: Differentially Expressed Genessupporting
confidence: 91%
“…The lack of LMP1 protein expression in some NPC samples may not accurately reflect the contribution of LMP1 to the pathology of NPC. In the transgenic mouse model, LMP1 expression led to epithelial hyperplasia, and yet LMP1 protein could not be readily detected with standard extraction methods (31). Here, we found that very small amounts of LMP1 that may be difficult to detect with currently available reagents, are sufficient to activate NF-B.…”
Section: Discussionmentioning
confidence: 73%
“…In epithelial cells, the CTAR1 domain of LMP1 signals through protein kinase C ␦ (PKC␦) and STAT3 to induce EGFR expression via a unique form of NF-B signaling wherein p50 dimers bind to BCL3 to regulate gene transcription (10,(16)(17)(18). Although LMP1 increases the transcription of the EGFR ligand, transforming growth factor-␣ (TGF-␣), TGF-␣ does not appear to be necessary for EGFR phosphorylation (19). Hence, it is unclear how LMP1 regulates EGFR activation.…”
Section: Importancementioning
confidence: 99%